Factors which determine the gastric secretory response to 2-deoxy-D-glucose. Issue 12 (December 1969) - Himsworth, R. L.; Colin-Jones, D. G.
Abstract : The physiological factors which determine the penetration of the brain by 2-deoxy-D-glucose have been studied and the practical importance of the blood-brain barrier has been demonstrated. The evaluation of the gastric secretory response to 2-deoxy-D-glucose has been shown to depend upon the plasma glucose concentration. It is concluded that because of the hazards and uncertainties in the use of 2-deoxy-D-glucose in man its use is to be deprecated.